Patenting Behaviour and Employment Growth in German Start-up Firms: A Panel Data Analysis - Michaela Niefert (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
The effect of innovations on employment at the firm level is theoretically ambiguous. The present paper analyses this relationship using panel data on German start-up firms as well as German patent data. It employs different indicators of patenting activity. By applying fixed-effects and first-differencing panel data methods it is shown that patenting activity has a positive effect on employment growth that is typically most pronounced in the second year after application. The effect seems to diminish with firm age. Patenting firms do not generally exhibit higher growth rates than their non-patenting counterparts; instead, growth performance depends on their patenting activity over time.
Keywords: C23; L25; D92; 330; employment growth; patents; Gibrats law; dynamic panel data models; Innovation; Patent; Personalbestand; Beschäftigung; Panel; Deutschland